Pelatihan Peningkatan Kemampuan Pengelolaan Blog Sebagai Media Informasi SMK Negeri 1 Kawunganten - Raden Bagus Bambang Sumantri; Arif Setia Sandi; Deny Nugroho Triwibowo; Budi Widadi (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
Abstract: Community Service (PkM) activity "Improving Weblog Management Capabilities with Internet Content as a means of information media for students of SMK Negeri 1 Kawunganten" which involved partners of junior high school students around. Many school students have not used weblogs to provide information and publications about activities related to learning, school organizational activities, and other activities. In this activity, partners will be given training on creating weblogs with internet content by the PKM team which is tailored to the level of needs and resources of each partner. At the end of this activity, it is hoped that all students who take part in the training can create a weblog by filling in healthy internet content for the better so that it will improve publication and information skills to internet users as a form of community service. The purpose of this service is to improve the weblog's ability to share students' knowledge, publications, and information by creating weblogs on the internet.Keywords: information; internet; weblog.Abstrak: Kegiatan Pengabdian Kepada Masyarakat (PkM) "Meningkatkan Kapabilitas Pengelolaan Weblog dengan konten internet untuk sarana media Informasi bagi siswa SMK Negeri 1 Kawunganten" yang melibatkan mitra siswa SMA/SMK. Banyak siswa sekolah belum menggunakan weblog untuk memberikan informasi dan publikasi tentang kegiatan yang berkaitan dengan pembelajaran, kegiatan organisasi sekolah dan kegiatan lainnya. Dalam kegiatan ini, mitra akan diberikan pelatihan pembuatan weblog dengan konten internet oleh tim PKM yang disesuaikan dengan tingkat kebutuhan dan sumber daya masing-masing mitra. Di akhir kegiatan ini, diharapkan seluruh siswa yang mengikuti pelatihan dapat membuat weblog dengan mengisi konten internet yang sehat menjadi lebih baik sehingga akan meningkatkan kemampuan publikasi dan informasi kepada pengguna internet sebagai bentuk pengabdian kepada masyarakat. Tujuan dari layanan ini adalah untuk meningkatkan kemampuan weblog untuk berbagi pengetahuan, publikasi dan informasi siswa dengan membuat weblog di internet.Kata Kunci:  informasi; internet; weblog